Beyond the Limits to Growth - Komiyama, Hiroshi (Science for Sustainable Societies, 2014)
Sustainable Development; Energy Policy, Economics and Management; Energy Efficiency (incl. Buildings); Climate Change Management and Policy; Renewable and Green Energy; Environmental Engineering/Biotechnology